2022
DOI: 10.1038/s41408-022-00626-4
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib with cyclophosphamide and dexamethasone in relapsed or refractory myeloma: MUKeight phase II randomised controlled trial results

Abstract: The all-oral combination of ixazomib, cyclophosphamide, and dexamethasone (ICD) is well tolerated and effective in newly diagnosed and relapsed multiple myeloma (MM). We carried out MUKeight, a randomised, controlled, open, parallel group, multi-centre phase II trial in patients with relapsed MM after prior treatment with thalidomide, lenalidomide, and a proteasome inhibitor (ISRCTN58227268), with the primary objective to test whether ICD has improved clinical activity compared to cyclophosphamide and dexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The median age of the patients ranged from 73 to 77 in the NDMM trials and 64 to 70 years in the R/R setting. Among the included RCTs, planned sample sizes ranging from N = 112 (Muk eight [ 19 ]) to N = 1852 (Myeloma XI [ 20 ]). Nineteen non-randomized studies (10 in NDMM and 9 in R/R) were included (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median age of the patients ranged from 73 to 77 in the NDMM trials and 64 to 70 years in the R/R setting. Among the included RCTs, planned sample sizes ranging from N = 112 (Muk eight [ 19 ]) to N = 1852 (Myeloma XI [ 20 ]). Nineteen non-randomized studies (10 in NDMM and 9 in R/R) were included (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the RCTs, in the NDMM studies, frailty prevalence ranged from 25.1% [ 50 ] to 54.0% [ 51 ]. In the R/R setting, many RCTs reported frailty prevalence as high as 73.6% as in the trial Muk eight [ 19 ]. Among the non-RCTs, frailty prevalence ranged from 17.2% [ 52 ] to 66.0% [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two recent phase Ib/II studies, OPZ003 (NCT01881789) and OPZ006 (NCT02072863), conducted in newly diagnosed MM, demonstrated that the use of Oprozomib in combination chemotherapy regimens exhibited gastrointestinal toxicities and variable pharmacokinetic (PK), suggesting that further optimization studies are needed [ 144 ]. To date, Ixazomib (MLN-9708), which binds to and blocks the 20S catalytic core of the proteasome, is the first and only orally available proteasome inhibitor approved by FDA for relapsed and refractory MM in combination with other antineoplastic drugs, as it was shown to be well tolerated and effective [ 145 , 146 , 147 ]. Furthermore, the use of Ixazomib as maintenance therapy extended the PFS of patients with newly diagnosed MM who did not undergo autologous stem cell transplantation; the drug was not associated with adverse effects [ 148 ].…”
Section: Therapeutic Targeting Of the Nf-κb Pathway In Cancermentioning
confidence: 99%